The Efficacy of Tembelekan Leaf Essential Oil (Lantana camara L.) as a Bioinsecticide for Aedes aegypti Mosquito Control - Selvi Marcellia; Citra Yuliyanda Pardilawati; Jhons Fatriyadi Suwandi; Benazhir Saninah Annasya; Linda Septiani (Warmadewa University, 2025)
Indonesia, as a tropical region, is susceptible to infectious diseases such as Dengue Fever (DHF), which poses a risk of mortality in humans. The management of DHF vectors can be achieved through the application of chemical insecticides; however, these may have detrimental effects on human health. Therefore, a remedy in the form of bioinsecticides is necessary. Tembelekan leaves contain numerous active components, including lantadine, essential oils, flavonoids, alkaloids, saponins, and tannins. This study aims to evaluate the efficacy of essential oil from tembelekan leaves (Lantana camara) as a bioinsecticide for killing Aedes aegypti mosquitoes. The research involved administering tembelekan leaf essential oil at concentrations of 0.5%, 0.75%, 1%, and 1.25%, with observations conducted at the 1st and 2nd hours, resulting in a mortality rate of approximately 10% to 95%. This indicates that the efficacy of tembelekan leaf essential oil falls within the effective category for exterminating mosquitoes. In conclusion, tembelekan leaf essential oil is effective in exterminating Aedes aegypti mosquitoes.